Influence of the use of Renewable Compatibility Agent Wood Plastic Composite (WPC) - Marin, Dielen; Chiarello, Luana M.; Gruber, Gisele K.; de Oliveira, Amanda D.; Reichert, Alexandra A.; Vieira, Kássia P.; Ender, Laércio; Wiggers, Vinicyus R.; Botton, Vanderleia (Journal of Research Updates in Polymer Science, 2022)
The growing interest in using recycled and natural materials in the application of new composites in recent years implies ecological, economic and versatility benefits. Wood plastic composite (WPC) are considered very attractive materials, as they allow the use of polymers of recycled or virgin origin, associated with forestry by-products. The present work aims to investigate the influence on the mechanical, thermal and morphological resistance of WPC, using oleic acid and glycerol as renewable coupling agents. Composites were also prepared with a commercial compatibility agent in its formulation - maleic anhydride grafted polypropylene (MAPP) - under the same conditions. The composites were prepared in a single-screw extruder, with fixed contents of 5% sawdust with 95% virgin polymer, of this total, 2% were coupling agents: MAPP, oleic acid or glycerol, according to the desired composition. To be evaluated as changes in mechanical properties, tensile and impact strength tests were performed on specimens obtained through the injection molding process. The fracture surfaces of specimens tested in tensile tests were examined using images generated by scanning electron microscopy. The thermal stability of the composites was also investigated by thermogravimetric analysis. The use of glycerol and oleic acid improved the mechanical properties of the composite. An increase in tensile strength is observed when glycerol is added in composite. As for impact strength, the addition of glycerol or oleic acid was around 58% higher in impact strength when compared to without coupling agent. Glycerol and oleic acid are renewable, low-cost alternative to be a potential substitute for the commercial coupling agent MAPP, especially when the main requirement is to obtain better impact resistance properties.